Optimasi Proses Pembelian Bahan Baku Melalui Sistem Informasi Berbasis Web - Adi Supriyatna; Carolina, Irmawati; Widiati, Wina (Jurnal Sistem Informasi Akuntansi, 2023)
The availability of raw materials is one of the important components in the production process. The availability of raw materials is also key in the production process at coffee shops/coffee shops. The process of recording raw material stocks in several coffee shops is still conventional. Meanwhile, in the process of ordering raw materials using social media such as Whatsapp. But there is no system between ordering raw materials and recording stock that is mutually integrated or computerized. This resulting in many discrepancies between data and items that do not match. Therefore, an information system is needed that can be used in the process of purchasing raw materials for making coffee. This study aims to design and implement a raw material purchasing information system in Coffee Shops that can assist Coffee Shop entrepreneurs in managing and monitoring raw material purchases in a structured and efficient manner. The research method used is the data collection method and the system development method Rapid Application Development (RAD). The result of this research is the creation of a web-based raw material purchasing information system that can minimize errors in the data processing process, make coffee shop performance more effective and efficient, and the raw material purchasing process becomes more accurate.